EFFICACY OF GARLIC EXTRACT±ASHWAGANDHA FOR THE TREATMENT OF INFECTIOUS REPEAT BREEDING IN CATTLE - LAWANGE, S R; MARKANDEYA, N M; KUMAWAT, B L; SAWALE, A G; ANBHULE, R S; KADAM, P D (The Indian Journal of Animal Reproduction, 2022)
The present research work was conducted to evaluate the efficacy of Garlic extract intrauterine (IU) versus Garlic extract (IU) plus Ashwagandha powder (oral) for the treatment of fresh (repeated ≤7 times) and chronic (repeated >7 times) infectious repeat breeding in cattle, respectively. Uterine infection was diagnosed by pH estimation, PMN cell count and White Side Test of cervico-vaginal mucus in both fresh and chronic cases while Immunoglobulin flocculation test with serum in chronic cases only. This indicated 92.8% cows having alkaline pH, PMN cell count >7% and 100% positive for White Side Test and increased immunoglobulin level in blood. Total 36 cows affected with endometritis were divided into three groups to undertake treatment on day of estrus viz. Group-I consisting of 12 fresh cases were treated with Garlic extract @10 μg in 30 ml PBS by intrauterine route once; Group-II consisting of 12 chronic cases were treated with Garlic extract as per Group-I plus Ashwagandha powder @ 15 gm with concentrates per oral for 5 days; and Group-III consisting of 12 cows as control were treated with placebo @ 30 ml PBS intrauterine. The clinical recovery of cows was confirmed by normal pH, negative white site test and PMN cell count <5% in cervico-vaginal mucus at subsequent estrus. Immunoglobulin flocculation test revealed raised immunoglobulin level in recovered cases of chronic endometritis. The recovered cows were inseminated with frozen-thawed semen at mid stage of estrus and pregnancy was confirmed at 50-60 day post insemination. The results of present investigation revealed highest recovery rate (83.3%) in group-I, whereas the highest conception rate (66.7%) and pregnancy rate (55.6%) was observed in group-II, thus suggesting the use of Garlic extract alomg with Ashwagandha for infectious repeat breeder cattle.